2023
DOI: 10.1101/2023.01.01.522328
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 protein NSP2 enhances microRNA-mediated translational repression

Abstract: microRNAs (miRNAs) inhibit mRNA translation initiation by recruiting the GIGYF2/4EHP translation repressor complex to the mRNA 5' cap structure. Viruses utilise miRNAs to impair the host antiviral immune system and facilitate viral infection by expressing their own miRNAs or co-opting cellular miRNAs. We recently reported that the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) encoded non-structural protein 2 (NSP2) interacts with GIGYF2. This interaction is critical for blocking translation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…An alternative mechanism has been reported for Sendai virus, where it boosts the production of the host interferon-stimulated genes ISG56 and ISGP54, which in turn inhibit translation initiation through binding to eIF3C and eIF3E, antagonizing eIF2-GTP-Met-tRNAi loading, and preventing the PIC recruitment to eIF3 (Guo et al, 2000; Hui et al, 2003; Terenzi et al, 2006). We previously reported that the SARS-CoV-2 derived NSP2 protein represses translation of Ifnb1 (Xu et al, 2022) and other mRNAs (Naeli et al, 2023b) through co-opting the GIGYF2/4EHP complex. However, NSP2 does not interact with GIGYF1 (Davies et al, 2020; Gordon et al, 2020; Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mechanism has been reported for Sendai virus, where it boosts the production of the host interferon-stimulated genes ISG56 and ISGP54, which in turn inhibit translation initiation through binding to eIF3C and eIF3E, antagonizing eIF2-GTP-Met-tRNAi loading, and preventing the PIC recruitment to eIF3 (Guo et al, 2000; Hui et al, 2003; Terenzi et al, 2006). We previously reported that the SARS-CoV-2 derived NSP2 protein represses translation of Ifnb1 (Xu et al, 2022) and other mRNAs (Naeli et al, 2023b) through co-opting the GIGYF2/4EHP complex. However, NSP2 does not interact with GIGYF1 (Davies et al, 2020; Gordon et al, 2020; Xu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…4EHP and GIGYF2 mediate the translational repression of mRNAs targeted by microRNAs [ 69 - 71 ]. NSP2 enhances the microRNA-induced translational silencing through interaction with GIGYF2 and stabilisation of the GIGYF2/4EHP complex [ 76 , 77 ]. Once thought to be exclusively a host-related mechanism, microRNAs are also expressed by viruses to control both host and viral gene expression [ 78 ].…”
Section: Mechanisms Of Evasion Of Ifn Production By Sars-cov-2mentioning
confidence: 99%